POTENSI BIOFUEL PADA MIKROALGA DENGAN VARIASI LIMBAH MENGGUNAKAN OXIDATION DITCH ALGAE REACTOR - Iqbal Ramadhan; Euis Nurul Hidayah; Savira Safrilia; Lolita Kurniasari; Aulia Ulfah Farahdiba; Ni Made Maya (EnviroUS, 2021)
This study describes the potential of microalgae biofuel using the oxidation ditch algae reactor. Production of biomass, chlorophyll a and lipids of Chlorella vulgaris increased with time and was observed to be 2440 mg / L, 3.78 mg / L, and 16.91% after 7 days, with tofu waste. Production of biomass, chlorophyll a and lipids was 2050 mg / l, 2.4 mg / l, 14.34%, with tannery waste. Production of biomass, chlorophyll a and lipids was 2430 mg / l, 3.47 mg / l, 16.79%. Production of biomass, chlorophyll a and lipids of Spirulina Plantesis increased with increasing time and it was observed that 3320 mg / L, 4.81 mg / L, and 23.86% after 7 days, with tofu waste the production of biomass, chlorophyll a and lipids increased with time. and observed 3210 mg / L, 2.67 mg / L, and 19.34% after 7 days, with waste from the tannery production of biomass, chlorophyll a and lipids of Spirulina Plantesis increased with increasing time and was observed to be 2980 mg / L, 4 mg / L, and 19.53% after 7 days. This study shows that biofuel production and wastewater treatment is made possible by Chlorella Vulgaris & Spirulina Plantesis using tofu waste & leather tanning waste